EPIDEMIOLOGY OF MALARIA DETERMINANTS IN CHILDREN IN PURWOREJO REGENCY (CASE CONTROL STUDY OF MALARIA IN CHILDREN IN 2022-2023) (Proceedings of the International Conference on Public Health, 2023)
Since 2019, Annual Parasite Incidence of malaria in Indonesia has increased from 0,9/ 1.000 to 1,1/ 1.000 people until 2021. Purworejo is a regency in Central Java with the high malaria cases, reach 544 cases with 129 cases in children 0-18 years in 2022. This study aims to analyze the risk factors for malaria in children 0-18 years in Purworejo. It is an analytic observational study with case control design. Case and control groups were selected based on the results of blood microscopic test. Data were analyzed univariately and bivariately using the chi square test with 0,05 degree of significance and presented in a cross table. This study recruited 154 parents/ guardians. From the results of bivariate analysis, malaria cases in children related with the existence of breeding places (p = 0,010), the existence of resting place (p = 0,037), knowledge of parents/ guardians (p = 0,001), and prevention practices by parents/ guardians (p = 0,035). Attitude of parents/ guardians (p = 0,159) and the existence of cattle pens (p = 0,127) were not related to the incidence of malaria in children. Child’s age (p = 0,007; OR = 0,341) is a protective factor for malaria in children. From the results of multivariate analysis, malaria in children caused by the existence of breeding place (p = 0,010; OR = 0,421; 95%CI = 0,218–0,814) and prevention practices of parents/ guardians (p = 0,036; OR = 2,028; 95%CI = 1,047–3,925) is a protective factor for malaria in children. Community education and vector control need to be improved considering malaria in children influenced by environmental and behavior of parents/guardians’ factors.
Keywords: malaria; children; risk factors